2015
DOI: 10.1097/mog.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertensive gastropathy and gastric antral vascular ectasia

Abstract: The treatment options for PHG and GAVE are constantly evolving and expanding. In this review, we present the latest approaches in the gastroenterologist's arsenal to deal with these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Splanchnic blood flow, distribution of gastric blood, various factors, local disturbances and portal pressure have been examined to elucidate the underlying mechanisms 26 . In addition to vascular alterations and gastric blood flow change, histological evidence of non-specific inflammation has been described in PHG, and around the blood vessels in the conjunctive of lamina propria appeared frequently inflammatory cell infiltrations and enhanced cytokine production appeared frequently 27,28 . By detecting the mucosa of the PVL-induced PHG mouse and patient samples, we found that, accompanying with inflammation infiltration, the levels of IL-1α , IL-1β , TNF-α , TGF-β , IL-6 , and ICAM-1 were markedly increased in PHG tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Splanchnic blood flow, distribution of gastric blood, various factors, local disturbances and portal pressure have been examined to elucidate the underlying mechanisms 26 . In addition to vascular alterations and gastric blood flow change, histological evidence of non-specific inflammation has been described in PHG, and around the blood vessels in the conjunctive of lamina propria appeared frequently inflammatory cell infiltrations and enhanced cytokine production appeared frequently 27,28 . By detecting the mucosa of the PVL-induced PHG mouse and patient samples, we found that, accompanying with inflammation infiltration, the levels of IL-1α , IL-1β , TNF-α , TGF-β , IL-6 , and ICAM-1 were markedly increased in PHG tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic treatment of PHG bleeding plays a highly limited role in the treatment of PHG because bleeding is always diffuse, and argon coagulation and sclerotherapy are only considered with focal bleeding. Surgical and transjugular intrahepatic portosystemic shunts are both invasive and are associated with substantial morbidity and mortality and would be considered only as a last resort in the management of excessive bleeding (Han et al, ). Therefore, in terms of prophylaxis and the management of PHG bleeding, there is little definitive data with which to make recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertensive gastropathy (PHG) is clinically important because it is a potential cause of gastric haemorrhage in patients afflicted with portal hypertension (McCormack et al, ; Cubillas and Rockey, ; Han et al, ; Massoni et al, ). Numerous elements, such as portal hypertension, PGs, TNF‐α and NO, have been demonstrated to participate in the pathogenesis of PHG (Patwardhan and Cardenas, ; Gjeorgjievski and Cappell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Initial management usually consists of adequate hydration and maximal doses of a proton pump inhibitor. Thereafter, non-selective β-blockers represent the mainstay of therapy for chronic bleeding, while somatostatin and vasopressin and their derivatives may be used in conjunction with supportive measures for acute bleeding and salvage therapy with trans-jugular intrahepatic portosystemic shunt or rarely surgical shunt is appropriate when medical management fails ( 2 , 17 , 18 ). The role of endoscopic therapy for PHG is controversial, and whereas balloon-occluded retrograde trans-venous obliteration presents an alternative approach for the management of PHG, liver transplantation should be considered as a final resort in cases of refractory bleeding due to PHG ( 2 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%